Une mobilisation « contre-nature » ? Le cas d’homosexuels opposés au mariage pour tous en France - Mickaël Durand (Genre, Sexualité et Société)
Based on semi-structured interviews this article analyzes the mobilization of conservative homosexual men who were involved in the movement against gay marriage in France in 2012-2013. The article shows that the logic of their mobilization lies in their conflictual relation to gay identity and LGBT activism. It argues that their opposition to gay identity and activism is not only rooted in the Catholic identity some of them share, but also in a logic of “status discontent”. Such a logic shows that belonging to traditional bourgeoisie or to Catholicism is not necessary for homosexuals to be against gay marriage.